Using ready-mixed mortars in concrete block structural masonry - Matos,Paulo Ricardo de (2020)
Abstract Ready-mixed mortars have been increasingly used due to their potential for waste reductions and productivity increases. However, research regarding their use in structural masonry applications are practically non-existent. Thus, this work investigated the technical feasibility of using ready-mixed mortars with nominal compressive strengths of 6, 9 and 14 MPa and storage times of 0 and 36 hours in concrete block structural masonry. The fresh state properties of the mortars were evaluated at 0 and 36 hours through the slump test, consistency and plasticity by the Gtec test, and entrained air content. The compressive and flexural strengths of the mortars were determined at 28 days. In addition, three-row prisms were tested for compressive strength and modulus of elasticity, and four-row prisms for flexural strength in the bending test, all at 28 days. The results showed that the 6 and 9 MPa ready-mixed mortars showed satisfactory maintenance of the fresh properties from 0 to 36 hours and adequate hardened properties for both casting ages, in contrast to the 14 MPa mortar. Regarding the prism tests, the increase in storage time did not significantly affect the properties evaluated for a reliability of 95%.